Factors affecting employee performance in Malacca State Development Corporation (MSDC) / Safilanatasa Eban and Nurul Izwana Razak - Eban, Safilanatasa; Razak, Nurul Izwana (Faculty of Business and Management, 2016)
The purpose of this research is to investigate the leadership, job satisfaction and co-worker relationship that influence employees’ performance in MSDC. Employee performance is important to management because attainment of a high-level performance through productivity and efficiency has always been an organizational goal of high priority. Based on the literature discussed, the three factors considered as the important elements influence the employees’ performance that need to be investigated. The research focuses on four objectives, which are first, to examine the impact of leadership on employee performance. Second is to find out the relationship between the job satisfaction and employee performance. Third is to determine co-worker relationship impact on employee performance. Lastly is to determine the factor that has the highest influence on employee performance. 110 respondents were chosen from the employees in MSDC by using simple convenience sampling. The findings of the study are, all three of the independent variables have significant relationship with employee performance. The researcher also found that co-worker relationship is the most significant predictor variable. Overall, the research objectives are able to answer in this study